Effect of pink guava oil-palm stearin blends and lard on dough properties and cookies quality - Abdul Rahman, Noor Raihana; Marikkar, Mohammed Nazrim; Jaswir, Irwandi; Ahmad Fadzlillah, Nurrulhidayah; Mat Sahri, Miskandar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
A study was carried out to compare the cookie dough properties and cookie quality made out of pink guava oil-palm stearin blends and lard (LD). Since LD is prohibited under religious restrictions, plant shortenings were prepared by mixing pink guava seed oil with palm stearin (PGO/PS) in different ratios: PGO-1, 40:60; PGO-2, 45:55; PGO-3, 50:50; PGO-4; 55:45 as replacement. The effect of these formulated plant-based shortenings and LD shortening were compared on dough rheological properties and cookie quality. Rheology and hardness of the cookie dough were evaluated using Texture Analyser (TA). Cookie hardness was evaluated with TA while cookie surface colors were measured using the CIE L*a*b* colorimetric system. Among the samples, cookies made out of PGO-2 with the ratio 45:55 (PGO:PS) performed the best substitute for LD to be used as shortening in cookies. PGO-2 also displayed the closest similarity to LD in cookies for hardness, size and thickness, cracking size as well as colour. As PGO-2 was a shortening formulated with plant-based ingredients, it could comply with the halal and toyyiban requirements.